Perils of Tight Clothing; A Survey Report - Sherazi, Syeda Abida Hussain; Awan , Wajid; Kazmi, Maira; Kanwal Mahmood; Awan , Anees Mahmood (Jurnal Medis Islam Internasional, 2021)
Background: Physical activity is defined as body movement produced by striated muscle that substantially increase utilization of energy, has numerous advantageous effect on the health. The level of physical activity influenced by different factors, include modifiable and non-modifiable factors. Non-modifiable factors include age, family history, sex and ethnicity. The modifiable factors include sedentary life style, lack of time, injury, body mass composition, socioeconomic level, leisure time and posture. Objective: To evaluate the effects of tight clothing on posture and physical activity, types of most frequent tight dress used by the participants, their effect on ADLs, problems caused by it & regions most commonly affected and plan for future. Methods: In this Cross-sectional study the convenient sampling technique was used. Females with the ages between 15 years to 55 years was included and those having physical disability and those diagnosed with medical problems were excluded. The Questionnaire was used to collect data after Consent was obtained from 186 participants. The SPSS was used for the statistical analysis. Result: The 80.6% (n=150) had low level of PA and 97.8% (n=182) had bad posture. Frequent used of tight clothing include underwear (99.5%, n=185) shirt (73.1%, n=136), jeans (43.5%, n=81), belt (90.3%, n=168), shoes (76.9%, n=143), sports gloves (95.7% n=178), bracelet (95.7%, n=178) and bra 98.4% (n=183). The most effected region was leg (n=102, 54.8%), low back (22.0%, n=41), foot (N=42, 22.6%), thigh (n=64, 34.4%), back (13.4%, n=25). Pain (65.6%, n=122), itching (46.2%, n=86), heaviness (41.9%, n=78), and numbness (18.8%, n=35 were the main problems observed due to tight clothing. The tight dress disturbs their ADLs (78.5%, n=146) the plan for change tight dressing (n=110,59%) also planning to used safety measure (n=137,73%). Conclusion: The tight dressing affects the physical activity and posture, leads to several problems in different regions, results in trouble while performing different physical activities. There is need to educate people about the use of proper and comfortable dress in daily routine and alert people about perils of tight dressing regarding posture and physical activity through social media, seminars and lectures. Keywords: Tight dressing, Clothing, Physical activity, Posture